Moving between doing and being-Meanings of person‐centredness as narrated by nursing home managers. A phenomenological hermeneutical study - Annica Backman; Karin Sjögren; Hugo Lövheim; David Edvardsson (Wiley, 2024)
Abstract Aim This study aimed to illuminate meanings of person‐centredness as narrated by nursing home managers in nursing homes rated as highly person‐centred. Design A phenomenological hermeneutical approach was used. Methods Twelve nursing home managers in 11 highly person‐centred nursing homes in 7 municipalities in Sweden were included in this interview study. The findings were interpreted, reflected and discussed through the lens of Ricoeur. Results Meanings of person‐centredness could be understand as moving between doing and being through knowing, sensing, sharing and giving for person‐centredness. These aspects contributed via knowledge, understanding, interaction and action that involved doing for and being with older persons through these caring dimensions. By moving between doing for, being with and being part of the overall nursing home narrative, knowing, sensing, sharing and giving could support the persons' identity in different ways. This may also contribute to sense‐making, preserving dignity and promoting self‐esteem when aiming to provide a good life for older persons in nursing homes, within an ever‐present ethical frame. No Patient or Public Contribution This study illuminated meanings of person‐centredness as narrated by nursing home managers. No patient of public contribution was investigated.